Critical success factors of paddy production at Kemubu Agricultural Development Authority (KADA) / Mohamad Safri Ya, Asry Yusoff and Nik Maheran Nik Muhammad - Ya, Mohamad Safri; Yusoff, Asry; Nik Muhammad, Nik Maheran
The research was conducted to understand the factors that can affect production of paddy. In this study, the researcher has narrowed down the scope by focusing on the paddy farming area in Kelantan. The research will be specifically conducted on the KADA paddy granary, which is the largest paddy granary. The study is important to help farmers increase their income by increasing production of paddy. In addition, increase in production of paddy is necessary since it can solve a few problems such as poverty rate, shortage of rice and deficit in trade balance. The data that has be used in this study are comes from both primary and secondary data. The results will be obtained by running a specific test by using SPSS 14. The result of this research is important in identifying the variables that has affect on the paddy production. Thus, its can help farmers and government in increasing paddy production. Since researcher provides several recommendations in order to increase the paddy production, researcher hopes that this will help farmers and government solving the problem that related with the paddy farming and boost the production of paddy in Malaysia.